Polish–Czech historical memory and the groundbreaking moments of common history - Wierzbiński, Szymon (Myths and Stereotypes in the Collective Representations, 2019)
It is not a secret that Czech nation played important role in Polish history. What is most striking, however, our southern neighbour do not occupy key position in Polish collective memory. It is worth considering why both nations are not closely integrated despite joint participation in so many seminal moments of history. In the first part of this paper I will aim at defining key events that shaped Czech collective memory. Next, I will make an attempt to answer why in some of these Polish and Czech people retained divergent visions of the past. Finally, I will try to point to some attempts undertaken by both nations in order to bridge the gaps in collective memory.